adding an additive inverse is the _______ as subtracting.

a - ____ = a + (-b)

(-5) - 3 = (-5) + (-3)
__=__

5 - (-6) = 5 + (6)
____ = 11

change the subtraction problem to adding the additive ________.

start at _______.

determine the direction according to the _______ of the numbers.
|-7| = __

1 answer

Let's complete the sentences step by step:

Adding an additive inverse is the same as subtracting.

a - b = a + (-b)

(-5) - 3 = (-5) + (-3)
-8 = -8

5 - (-6) = 5 + (6)
11 = 11

Change the subtraction problem to adding the additive inverse.

Start at the first number.

Determine the direction according to the sign of the numbers.
|-7| = 7

Similar Questions
  1. 3 Vocabulary Terms - Define/IllustrateAdding/Subtracting Fractions - we need a _______________ Adding/Subtracting expressions -
    1. answers icon 1 answer
  2. 1. Adding/Subtracting Fractions - we need a _______________2. Adding/Subtracting expressions - we need ______________
    1. answers icon 1 answer
  3. 1. Adding/Subtracting Fractions - we need a _______________2. Adding/Subtracting expressions - we need ______________
    1. answers icon 3 answers
  4. How is adding and subtractingradicals the same as adding and subtracting polynomials?
    1. answers icon 2 answers
more similar questions